Borderline hemoglobin A2 levels in northern Thai population: HBB genotypes and effects of coinherited alpha-thalassemia - Phumin Chaweephisal (2018)
© 2018 Elsevier Inc. Introduction: Identification of beta-thalassemia carrier in prenatal screening relies on the elevated Hb A2 level. Borderline Hb A2 levels pose a diagnostic challenge. We determined the HBB genotypes in subjects with borderline Hb A2 in northern Thailand and studied the effects of coinherited alpha0-thalassemia on Hb A2 levels. Methods: Blood samples with Hb A2 3.1–10.0% from 2193 samples submitted for prenatal thalassemia screening were selected. Information on HBB genotypes and coinherited alpha0-thalassemia were collected. All samples with unknown HBB genotypes underwent an automated DNA sequencing. The Hb A2 levels were compared according to the coinherited alpha0-thalassemia. Results: HBB mutations were found in 298 (98.7%) of 302 samples with Hb A2 4.0–10.0%. In the 106 samples with Hb A2 3.1–3.9%, six had HBB mutations; four Hb Dhonburi [codon 126 (T > G)], one CAP site mutation [CAP + 1 (A > C)] and one beta0-thalassemia [codon 41/42 (-TTCT)] with a coinherited HBD mutation [nt-77 (T > C)]. The Hb A2 levels in beta-thalassemia carriers with and without coinherited alpha0-thalassemia were not significantly different. Conclusions: HBB mutations in northern Thais with borderline Hb A2 levels comprise an unstable variant Hb Dhonburi and CAP + 1 (A > C) mutation. Coinherited HBD mutation lowers Hb A2 and can cause a misidentification of a beta-thalassemia carrier.